Blended architectural design studio learning for resilient architecture education / Sayed Muhammad Aiman Sayed Abul Khair ... [et al.] - Sayed Abul Khair, Sayed Muhammad Aiman; Mohd, Thuraiya; Mahayuddin, Siti Akhtar; Zainal Abidin, Mohammad Nazrin; Yusserie, Farid Al Hakeem (2022)
The spread of the COVID-19 pandemic has changed the landscape of the nation's education system. Such closure accelerated the development of the online learning environments within those institutions so that learning would not be disrupted. The pandemic has tested the readiness of centres to deal with a crisis that requires online and remote measures. HEIs need to implement classes with various online methods to ensure learning continues. However, lack of face-to-face interactions between learners, learners and instructors, and the effectiveness of online learning is called into doubt. The architectural design studio also struggled to adjust to this event due to the socially involved aspects of design education and learning, which many design tutors say make it difficult, if not impossible, to teach design online. As a result, learning engagement and belonging in architectural design studios suffer from this strategy. This paper aims to review students' and educators' experience teaching and learning on the effects of online learning during this pandemic. Thus, literature has been reviewed on the impact of online learning during this pandemic, which caters to several aspects of students' and academicians' feedback and architectural design studio in digital platforms. This paper presented the concept of blended learning, which combines the benefits of synchronous critiques and asynchronous learning and allows for cross-time and cross-space engagement with institutions and experts. The findings suggested that students may have difficulties dealing with technology, particularly in terms of usage and acceptance by students. Students' acceptance and use are significant for the academicians to be well-designed and well-prepared the course plan, contents, and instructions within the digital platform. This study's findings will significantly contribute towards teaching and learning experience and as a guideline for educators and policymakers to implement the blended learning platform as an alternative to traditional learning approaches.